Submission of Rifaximin to Different Techniques: Characterization, Solubility Study, and Microbiological Evaluation - Kogawa, Ana Carolina [UNESP]; Peltonen, Leena; Antonio, Selma Gutierrez [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Springer Nature, 2019)
Rifaximin, an oral antimicrobial drug, is marketed as 200-mg tablets. The daily dose ranges from 600 mg (1 tablet 3 times a day) to 800 mg (2 tablets twice a day). It is used for a wide range of ages, from adults to children, since it is indicated for the treatment of hepatic encephalopathy, travelers’ diarrhea, irritable bowel syndrome, Clostridium difficile, ulcerative colitis, and acute diarrhea. The success of pharmacotherapy will depend on correct fulfillment of drug administration; however, it becomes difficult when the tablets are large and the doses are frequent. Rifaximin belongs to class IV according to the Biopharmaceutic Classification System (BCS), meaning that it is both poorly soluble and poorly permeable. Thus, in this study, solubility of rifaximin was improved by its complexation to β-cyclodextrin by (i) phase solubility diagram, (ii) malaxation, and (iii) decreasing particle size by wet milling. Improved solubility provides lower doses and facilitates compliance with pharmacotherapy. The products formed were analyzed by spectrophotometry in the infrared region (FT-IR), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). Also, their solubility and microbiological activity were determined. The products obtained in all techniques were more soluble than the free drug; they presented higher thermal stability and antimicrobial potency was approximately 100% with all the formulations. It is important to highlight that the treatment failure not only affects the quality of life of the patients, but also contributes significantly to the economic burden of the health system. Therefore, these findings are extremely interesting, both from a technological and financial point of view.
Keywords: malaxation; phase solubility diagram; rifaximin; wet milling; β-cyclodextrin